Curcumin analog, GO-Y078, induces HO-1 transactivation-mediated apoptotic cell death of oral cancer cells by triggering MAPK pathways and AP-1 DNA-binding activity. (3rd April 2022) - Chien, Ming-Hsien; Shih, Pei-Chun; Ding, Yi-Fang; Chen, Li-Hsin; Hsieh, Feng-Koo; Tsai, Meng-Ying; Li, Pei-Yi; Lin, Chiao-Wen; Yang, Shun-Fa
ABSTRACT: Background: GO-Y078, a new synthetic analogue of curcumin (CUR), has higher oral bioavailability and anticancer activity than CUR, but the oncostatic effect of GO-Y078 on oral squamous cell carcinoma (OSCC) is largely unknown. Research design and methods: In the present study, we examined the oncostatic properties and possible mechanisms of GO-Y078 on human SCC-9 and HSC-3 OSCC cells. Results: Our results indicated that GO-Y078 showed a cytostatic effect against OSCC cells, and this antiproliferative phenomenon stemmed from a mechanism involving multiple levels of cooperation, including cell-cycle G2 /M arrest and apoptosis induction. Mechanistically, GO-Y078 treatment induced caspase-mediated apoptosis via upregulating two apoptosis-modulating proteins, SMAC/DIABLO and heme oxygenase (HO)-1. GO-Y078 transcriptionally induced upregulation of the HO-1 gene by increasing the AP-1 DNA-binding activity, which was initiated by activation of the p38 /JNK1/2 pathways. In the clinic, patients with head and neck cancers expressed lower HO-1 and SMAC/DIABLO levels in primary cancer tissues compared to normal tissues. Clinical datasets also revealed that patients with head and neck cancers expressing high HO-1 had afavorable prognosis. Conclusions: Our results provide new insights into the role of GO-Y078-induced molecular regulation in suppressing OSCC growth and suggest that GO-Y078 has potential therapeutic applications for OSCC.